PERAN ADVOKAT DALAM MENEGAKKAN KEADILAN BERDASARKAN PRINSIP- PRINSIP SYARIAT ISLAM - Muhammad Fadil Zuhri; Wahyuni Pohan, Muhammad Rizki Firmansyah, Ayu Hijrani Salamah, Aditya Dwipa Alkanzu (CV. ADIBA AISHA AMIRA, 2025)
The role of advocates in upholding justice is firmly rooted in the principles of Islamic Sharia, which highly values honesty, trustworthiness, and fairness. Advocates serve as legal representatives tasked with assisting, defending, and representing clients in resolving legal disputes. From the perspective of Islamic Sharia, this practice aligns with the concept of wakalah (representation), which is permissible as long as it is carried out with good intentions, integrity, and adherence to Sharia laws. The principle of justice, which is a cornerstone of Islamic Sharia, demands that advocates perform their duties impartially, ensuring that their clients' rights are protected while avoiding any defense based on falsehood. Advocates also bear a moral responsibility to uphold the truth, as emphasized by the teachings of the Prophet Muhammad (peace be upon him), which stress the importance of providing accurate testimony and not concealing evidence. Thus, the advocates profession in Islam is not only regarded as a worldly occupation but also as a trust imbued with a spiritual dimension, as long as it is conducted with integrity and adheres to the principles of Sharia, namely the Quran and Sunnah.